The Effect of Physical Activity on the Prevention and Management of Burnout Syndrome in Nurses: A Literature Review - Kiškytė-Zapolskė, Aurelija; Miežienė, Brigita; Giliun, Renata (Slauga. Mokslas ir praktika, 2025)
Psychological burnout is one of the most pressing problems facing modern healthcare professionals, especially nurses. Research reveals that more than a quarter of nurses in the European Union (EU) countries experience burnout. This creates the need to take active steps to address the issue. Physical activity (PA) is one of the potentially effective ways that can help reduce burnout symptoms and promote mental well-being. The aim of the study was to analyse the scientific literature examining the effects of physical activity on the prevention and management of the burnout syndrome in nurses. A review of scientific articles has been conducted using keywords and their combinations. Scientific articles were searched in international databases PubMed, Web of Science and in the specialised information search system Google Scholar. The PRISMA flow diagram was applied to the search results. The systematic review included 9 articles on the subject. Results: Nurses experienced high levels of burnout, and most of them were physically inactive. Nurses with low PA levels were more likely to experience fatigue and burnout. PA has a positive effect on nurses’ emotional balance, helping them cope with burnout symptoms. PA interventions help nurses manage burnout more effectively and act as a means of preventing burnout. Conclusions: The analysis reveals that PA has a positive effect on the management and prevention of burnout in nurses. It has been established that regular, recreational PA in nurses can suppress the expression of burnout, increase job satisfaction, and improve the physical and psychological health of nurses. In order to ensure regular PA in nurses, special programs and interventions are needed.
Keywords: burnout syndrome; psychological burnout; physical activity; prevention and management of burnout